Photon-counting computed tomography: basic principles, potenzial benefits, and initial clinical experience: review - Stein, Thomas; Rau, Alexander; Russe, Maximilian Frederik; Arnold, Philipp; Faby, Sebastian; Ulzheimer, Stefan; Weis, Meike; Froelich, Matthias F.; Overhoff, Daniel; Horger, Marius; Hagen, Florian; Bongers, Malte; et al. (RöFo, 2023)
Background: Photon-counting computed tomography (PCCT) is a promising new technology with the potential to fundamentally change today’s workflows in the daily routine and to provide new quantitative imaging information to improve clinical decision-making and patient management. Method: The content of this review is based on an unrestricted literature search on PubMed and Google Scholar using the search terms “Photon-Counting CT”, “Photon-Counting detector”, “spectral CT”, “Computed Tomography” as well as on the authors’ experience. Results: The fundamental difference with respect to the currently established energy-integrating CT detectors is that PCCT allows counting of every single photon at the detector level. Based on the identified literature, PCCT phantom measurements and initial clinical studies have demonstrated that the new technology allows improved spatial resolution, reduced image noise, and new possibilities for advanced quantitative image postprocessing. Conclusion: For clinical practice, the potential benefits include fewer beam hardening artifacts, radiation dose reduction, and the use of new contrast agents. In this review, we will discuss basic technical principles and potential clinical benefits and demonstrate first clinical use cases.
Online veröffentlicht: 02.03.2023
Gesehen am 04.04.2024